Birth Month as a Risk Factor for the Diagnosis of Celiac Disease Later in Life: A Population-based Study. Issue 3 (September 2018) - Assa, Amit; Waisbourd-Zinman, Orith; Daher, Saleh; Shamir, Raanan
Abstract : ABSTRACT: Various perinatal factors have been implicated in association with the risk of developing celiac disease (CD) in genetically susceptible individuals. Our aim was to investigate the association of month and season of birth with the development of CD later in life in a large National cohort in Israel. Data were retrieved from a National database of more than 2 million Israeli Jewish adolescents born between 1971 and 1998. Overall, 10, 566 CD cases out of 2, 001, 353 subjects (0.53%) were identified and analyzed. CD risk was significantly higher for subjects born in May (odds ratio [OR] 1.07, P = 0.04) and June (OR 1.09, P = 0.008). Birth during the winter season (December to February) showed a marginal significance toward reduced risk (OR 0.97, P = 0.05). In conclusion, children born in May and June are at increased risk for CD. This increased risk provides further evidence that perinatal environmental factors increase the risk of developing CD.